Customary criminal law in the Eastern of Indonesia: the special autonomy Province of Papua - Aisy, Salsabila Rahadatulâ€™; Hakim, Hary Abdul; Krisnan, Johny; Hardyanthi, Try; Masithoh, Mutia Qori Dewi (Borobudur Law Review, 2021)
Autonomy is often seen as an institutional instrument to manage sub state nationalist conflict. Its implementation is also a key in determining its impact on conflict. After the reform period 1999 â€œAutonomy and Decentralizationâ€ in Indonesia are widely welcomed. While Papua is an inseparable part of special autonomy in Indonesia. Papua as a former Dutch territory which was later handed over to Indonesia has many advantages, both in terms of culture, customary law and natural resources. But on the other hand, the fact is that the indigenous Papuan people does not agree to join as part of Indonesian territory. This rejection was accompanied by separatist actions based on their interest mentioned in the memorandum for Papuan independence. This research is the first to aim to measure whether the special autonomy given to Papua has been effectively carried out in an effort to defend Papua as a part of Indonesia. Second, in the application of this special autonomy related to the existent of customary criminal law in papua. The research used normative legal research by statute approach, the data collected through library research and also analysed used descriptive qualitative. So it is concluded that the application of the special autonomy given to Papua has a big impact on democracy in Indonesia, as well as the Papua regional government given specialization in managing its regional potential. Although there are still problems in its implementation.